CO2 Adsorption on HZSM-5 Zeolite : Mass Transport Study in A Packed Bed Adsorber - Sang Kompiang Wirawan; Ihda Novia Indrajati; Wahyudi Budi Sediawan; Panut Mulyono; Derek Creaser (ASEAN Journal of Chemical Engineering, 2008)
Experimental and modeling have been done to study and to determine the diffusion parameters of CO2 adsorption on HZSM-5 zeolite in a packedbed adsorber. Experiment works consisted of tracer and adsorption experiments. The feed gas concentrations were 40 and 80% CO2 in helium within various temperatures of 373, 423 and 473 K. The experiments were conducted by using transient step change adsorption. Tracer experiments using 20% Ar/He were conducted to measure dispersion and time lag effect of the packed bed system. A model of CO2 adsorption on HZSM5 had been set up for transient packedbed adsorber by assuming plug flow, isothermal and isobaric, single site Langmuir physisorption, no gas film mass transport resistance and MaxwellStefan mass transport in micropore applied. All the data were then optimized to get the best value of modified fitted parameter. The results indicated that at higher temperature, the quantities of gas adsorbed were decrease. This was due to lower adsorption capacity which occurs at higher temperature. The model was in a good agreement with the experiment data. Diffusivity tended to increase by increasing temperatures.